Spatial analysis of measles vaccination coverage in the State of São Paulo - Ysabely de Aguiar Pontes Pamplona; Anderson Marcos Vieira do Nascimento; Ricardo Alves de Olinda; Carolina Luisa Alves Barbieri; Alfésio Luís Ferreira Braga; Lourdes Conceição Martins (BMC, 2023)
Abstract Background Measles is a contagious viral disease that seriously affects children. The measles vaccine is widely recommended in Brazil and in the world; however, the disease remains relevant for the health authorities. The aim of the present study was to evaluate first and second dose of measles vaccine coverage (VC) in the cities of São Paulo and its spatial dynamics between 2015 and 2020. Method: In this mixed-type ecological study, we used secondary, public domain data from 2015 to 2020, extracted from the Digital Information System of the National Immunization Program, Mortality Information System and the National Live Birth Information System. After calculating the VC, the following four categories were created: very low, low, adequate, and high, and the spatial autocorrelation of VC was analyzed using the Global and Local Moran's statistics. Results A steady decline in adherence to the vaccination was observed, which dynamically worsened until 2020, with a high number of cities fitting the classification of ineffective coverage and being potentially harmful to the effectiveness of the immunization activities of their neighbors. Conclusion A direct neighborhood pattern was observed between the units with low vaccination coverage, which implied that the reduction in measles VC was somehow related to and negatively influenced by the geographic location and social culture of these areas.